INTEGRATION OF EDUCATION, SCIENCE, AND BUSINESS: CURRENT INSTITUTIONAL SOLUTIONS - V. S. SHEINBAUM; O. V. BUDZINSKAYA (Высшее образование в России)
The article discusses the problem of a lack of a national-level institutional solution to the problem of integration of education, science and business in Russia. For the purposes to develop recommendations, proven forms of integration based on international practices are reviewed and applied to Gubkin University. In developed world economies, integration of science and education is associated with technologization, the transition to knowledge-based industry embodied in the form of advanced structural amalgamations, such as Silicon Valley entities – clusters, technology parks and business incubators. Integration of academic and business communities is effected through the participation of business in the management of universities, both in the sphere of education by establishing close relations between competences highly demanded by the labor market and competences offered by higher education institutions, and in terms of administration of a university as a whole in its capacity as an economic agent. This interaction is implemented using various mechanisms that are discussed in detail in the article.